Therapeutic and preventive effects of astaxanthin in ischemic stroke - Wang, Xu; Li, Hongyan; Wang, Gaihua; He, Ziqiao; Cui, Xueting; Song, Feiyu; Li, Jinhua; Zhang, Lin (Frontiers in Nutrition, 2024)
Ischemic stroke poses a significant global health challenge with limited treatment options. Tissue plasminogen activator, the only effective medication, has strict restrictions, limiting its benefits only to a small number of patients. Astaxanthin, a natural carotenoid found in algae, shrimp, and crabs, has demonstrated promising neuroprotective properties in models of ischemic stroke. This article reviews the novel finding of neuroprotective impact of astaxanthin in ischemic stroke, highlighting its benefits in various protective mechanisms such as antioxidation, anti-inflammation, enhancement of DNA repair, anti-cell death, protection of blood–brain barrier, and promotion of neuronal survival. This analysis underscores the therapeutic and preventive potential of astaxanthin in ischemic stroke, positioning it as a prospective pharmaceutical agent against ischemic stroke.